Herpes simple tipo I en periodoncia - Molano, Pablo E. (Revista Estomatología, 1996)
The object of this review work, is to show the reader the standard physiopato]ogy of the herpes virus type one, the imp]ication this one has in orofacia] and periodonta] leve] and treatment methodes that have been used to inhibit this action.